2012
DOI: 10.1259/dmfr/57281042
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced CT and MRI for detecting neck metastasis of oral cancer: comparison between analyses performed by oral and medical radiologists

Abstract: Objectives: The aim of the study was to verify the concordance of contrast-enhanced CT (CECT) and MRI evaluation among four radiologists in detecting metastatic cervical lymph nodes of oral cancer patients. Methods: Ten patients underwent clinical and imaging examinations (CECT and MRI). Four radiologists, two oral and maxillofacial radiologists (OMRs) and two medical radiologists (MRs), independently analysed the images twice. Cohen's kappa index and Wilcoxon signed-rank test were used to verify the concordan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Subspecialisation may also play a role, with many radiologists in human medicine focusing on specific anatomic sites or organ systems, whereas veterinary radiologists typically cover all anatomic sites for a wide range of species. Greater agreement in assessment of cervical lymph node metastasis has been reported between oral and maxillofacial radiologists when compared with medical radiologists supporting the concept that even within radiologists assessing a single species, subspecialisation provides a benefit for assessment of lymph nodes …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subspecialisation may also play a role, with many radiologists in human medicine focusing on specific anatomic sites or organ systems, whereas veterinary radiologists typically cover all anatomic sites for a wide range of species. Greater agreement in assessment of cervical lymph node metastasis has been reported between oral and maxillofacial radiologists when compared with medical radiologists supporting the concept that even within radiologists assessing a single species, subspecialisation provides a benefit for assessment of lymph nodes …”
Section: Discussionmentioning
confidence: 99%
“…Greater agreement in assessment of cervical lymph node metastasis has been reported between oral and maxillofacial radiologists when compared with medical radiologists supporting the concept that even within radiologists assessing a single species, subspecialisation provides a benefit for assessment of lymph nodes. 36 Ultimately, a patient is staged as a whole, rather than just a single site. Computed tomography will continue to play an important role in staging of local disease and pulmonary metastasis, but, given the limitations identified in this study, alternative methods must be considered for lymph node staging.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared to MRI, CT has advantages of lower price, shorter inspection times, and less contraindications, especially for patients with dental artifacts (33). In some studies, CECT outperforms MRI in detecting neck metastasis and assessment of tumor depth of invasion in oral cancer (34,35). Hence in TSCC, CECT is used more widely than MRI, which makes the research of CECT in TSCC more meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…CECT and magnetic resonance imaging (MRI) are prominent imaging modalities for assessing lymph node involvement across various cancers. Numerous studies have sought to compare the diagnostic accuracy of these techniques [ 36 ]. For instance, a study by Chen et al focusing on nasopharyngeal carcinoma (NPC) revealed that MRI outperformed CECT in detecting retropharyngeal lymph node (RLN) metastases.…”
Section: Reviewmentioning
confidence: 99%